1, 25‐Dihydroxyvitamin D3‐induced intestinal calcium transport is impaired in β‐globin knockout thalassemic mice. (1st February 2013) - Charoenphandhu, Narattaphol; Kraidith, Kamonshanok; Teerapornpuntakit, Jarinthorn; Thongchote, Kanogwun; Khuituan, Pissared; Svasti, Saovaros; Krishnamra, Nateetip
<x xml:space="preserve">Abstract</x> Besides being a common haematological disorder caused by a reduction in β‐globin production, β‐thalassemia has been reported to impair body calcium homeostasis, leading to massive bone loss and increased fracture risk. Here, we demonstrated that heterozygous β‐globin knockout thalassemic mice had a lower rate of duodenal calcium absorption compared with the wild‐type littermates, whereas the epithelial electrical parameters, including transepithelial resistance, were not affected, suggesting no change in the epithelial integrity and permeability. Daily subcutaneous injection of 1 µg kg−1 1, 25‐dihydroxyvitamin D3 [1, 25(OH)2D3] for 3 days enhanced the duodenal calcium absorption in wild‐type, but not in thalassemic mice. Although β‐thalassemia increased the mRNA level of divalent metal transporter‐1, an iron transporter in the duodenum, it had no effect on the transcripts of ferroportin‐1 or the principal calcium transporters. In conclusion, β‐thalassemia impaired the 1, 25(OH)2D3‐dependent intestinal calcium absorption at the post‐transcriptional level, which, in turn, contributed to the dysregulation of body calcium metabolism and β‐thalassemia‐induced osteopenia. Copyright © 2013 John Wiley & Sons, Ltd.